2016
DOI: 10.15244/pjoes/62997
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Constituents of Edible Field Parasol (Macrolepiota procera) Mushrooms and the Underlying Substrate from Upland Regions of Poland: Bioconcentration Potential, Intake Benefits, and Toxicological Risk

Abstract: Fungi play a key role in the transfer of metals from the lithosphere into the biosphere. Within the biodiverse world, mushrooms are the important groups that constitute edible and medicinal mushrooms. Most of the estimated 2,000 species of edible wild mushrooms that grow worldwide are poorly characterized with respect to their composition and multi-mineral constituents as well as their bio-accessibility, while such information is completely absent for numerous species. In the studies of metallic elements and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
(71 reference statements)
5
15
0
Order By: Relevance
“…Particularly, wild growing mushrooms play an important role in the cycle of organic matter and trace element because they are able to degrade the organic substrate (saprophytic fungi) and/or coexist with the host organism (mycorrhizal fungi) and thus close the biological cycle in the forest ecosystem (Gupta et al, 2014;Petkovšek and Pokorny, 2013;Ouzouni et al, 2009). In combination with their characteristic high bioaccumulative capacity for risk elements (mainly saprophytic fungi) they reduce the content of xenobiotics in other environmental compartments (Árvay et al, 2017;Kojta et al, 2016;Stefanović et al, 2016;Angelovičová and Fazekašová 2014) at the expense of increasing content of the contaminants in their fructification organs (Slávik et al, 2013). Many studies show that the quality of the environment is a significant factor affecting the content of the risk elements in the above-ground parts of mushrooms, as well as plants and/or products (Falandysz 2017;Širić et al, 2017;Stanovič et al, 2016;Mleczek et al, 2015;Árvay et al, 2014;Tomáš et al, 2014;Mleczek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, wild growing mushrooms play an important role in the cycle of organic matter and trace element because they are able to degrade the organic substrate (saprophytic fungi) and/or coexist with the host organism (mycorrhizal fungi) and thus close the biological cycle in the forest ecosystem (Gupta et al, 2014;Petkovšek and Pokorny, 2013;Ouzouni et al, 2009). In combination with their characteristic high bioaccumulative capacity for risk elements (mainly saprophytic fungi) they reduce the content of xenobiotics in other environmental compartments (Árvay et al, 2017;Kojta et al, 2016;Stefanović et al, 2016;Angelovičová and Fazekašová 2014) at the expense of increasing content of the contaminants in their fructification organs (Slávik et al, 2013). Many studies show that the quality of the environment is a significant factor affecting the content of the risk elements in the above-ground parts of mushrooms, as well as plants and/or products (Falandysz 2017;Širić et al, 2017;Stanovič et al, 2016;Mleczek et al, 2015;Árvay et al, 2014;Tomáš et al, 2014;Mleczek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3b). Theoretically, these signals have identical T 1 and NOE values, which means the average polymerization degree could be calculated by integrating these signals [34]. Unfortunately, in the case of the spectra presented here the signal-to-noise ratio is too low for such quantification.…”
Section: Nmr Spectramentioning
confidence: 99%
“…In this process, a huge quantity of water and inorganic and organic chemicals are used, thereby discharging solid and liquid wastes into the environment [1][2][3]. It is calculated that about 450 kg of solid waste as well as 50 m 3 of wastewater are released for every 200 kg of leather produced [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to understand the role of soil bedrock geochemistry and soil pollution in accumulation of toxic elements in fruiting bodies of mushrooms foraged in Europe . A few recent studies have shown that edible mushroom species growing in background (unpolluted) areas can accumulate Cd and Hg at level well above the content in soil substrate, while some mushrooms hyper accumulate As, Cd, Hg and Pb in the mining and geoanomalous areas . Heavy metal intake through consumption of metal‐tainted food is of interest because of their essential or toxic properties.…”
Section: Introductionmentioning
confidence: 99%